2017
DOI: 10.1055/s-0037-1599109
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Feeding Disorders and Severe Developmental Disabilities

Abstract: Children with severe developmental disabilities face numerous challenges to function and participate in activities of daily life. One of the most significant challenges to accomplishing this goal is that of oral feeding disorders. Indeed, it is estimated that among children with developmental disabilities, up to 80 to 90% present with some level of feeding disorders. In addition, it has been shown that as the level of severity of intellectual disability increases, so does the severity of the oral feeding disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 31 publications
0
5
0
3
Order By: Relevance
“…To evaluate this relationship, we once again began with the genetics of human developmental disorders and their consequences for morphological and behavioral disruption. The incidence of S/F/S difficulties from birth through early childhood -collectively referred to as pediatric dysphagia -is significantly elevated in genetic developmental syndromes as well as children with clinically diagnosed behavioral neurodevelopmental disorders (Berlin et al, 2011;Kleinert, 2017;Robertson et al, 2017;Bianco and Rota, 2018;Maynard et al, 2020b;Nordstrom et al, 2020), including infants and toddlers with 22q11DS (Eicher et al, 2000). Craniofacial and brain anomalies characterize all of these developmental disorders, including 22q11DS.…”
Section: Putting It Together: Face Brain and Behaviormentioning
confidence: 99%
“…To evaluate this relationship, we once again began with the genetics of human developmental disorders and their consequences for morphological and behavioral disruption. The incidence of S/F/S difficulties from birth through early childhood -collectively referred to as pediatric dysphagia -is significantly elevated in genetic developmental syndromes as well as children with clinically diagnosed behavioral neurodevelopmental disorders (Berlin et al, 2011;Kleinert, 2017;Robertson et al, 2017;Bianco and Rota, 2018;Maynard et al, 2020b;Nordstrom et al, 2020), including infants and toddlers with 22q11DS (Eicher et al, 2000). Craniofacial and brain anomalies characterize all of these developmental disorders, including 22q11DS.…”
Section: Putting It Together: Face Brain and Behaviormentioning
confidence: 99%
“…Es importante mencionar que las dificultades de la deglución en muchas ocasiones podrían ser causantes de experiencias negativas por sí mismas lo que generaría dificultades asociadas. Kleinert, 2017).…”
Section: Discussionunclassified
“…The prevalence of pediatric feeding disorders (PFD) among infants and children ranges between 10% and 32% (Kovacic et al, 2021; Stewart et al, 2019) with higher rates reported for infants and children with developmental disabilities (Kleinert, 2017; Mercado‐Deane et al, 2001; Milnes & Piazza, 2013; Motion, Northstone, Emond,, & Team, 2001; Uhm et al, 2013). It is estimated that between 30% and 50% of infants and children with PFD demonstrate oropharyngeal aspiration (abbreviated to aspiration), where fluids enter the trachea below the level of the vocal cords pre‐, during and/or post‐swallowing (Frakking et al, 2016; Patel et al, 2020; Uhm et al, 2013; Weir et al, 2011).…”
Section: Introductionmentioning
confidence: 99%